Cognitive dysfunction, dissociation and quality of life in bipolar affective disorders in remission - Latalova, Klara; Prasko, Jan; Diveky, Tomas; Kamaradova, Dana; Velartova, Hana (Psychiatria Danubina, 2010)
BACKGROUND: Bipolar disorders are often associated with cognitive deficits, which have an influence on social functioning and the course of the illness. These deficits have an impact on occupational ability and social integration. SUBJECTS AND METHODS: To ascertain cognitive function, level of dissociation and quality of life and their interrelations in patients with bipolar affective disorder in remission. Data from D2 Attention Test, Verbal Fluency Test and Trial Making Test, Dissociative Experiences Scale (DES). Quality of Life Satisfaction and Enjoyment (Q-LES-Q) and M.I.N.I. (MINI-international neuropsychiatric interview were statistically analyzed. RESULTS: There are no significant correlations between applied cognitive tests and dissociation scale DES. There are no significant correlations between applied cognitive tests and dissociation scale DES. There were no differences between employed and unemployed patients in DES, pathological DES and in any of Q-.LES-Q domains. CONCLUSIONS: We need further research to explore the role of cognitive functions and dissociation in bipolar affective disorder and its relationship to cognitive functions, emotional regulation, biological factors and therapy outcome.
Keywords: Humans; neuropsychologické testy; lidé středního věku; International Classification of Diseases; Attention; Quality of Life; Female; dospělí; lidé; kvalita života; Dissociative Disorders; bipolární porucha; indukce remise; Adult; Cognition Disorders; Neuropsychological Tests; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Bipolar Disorder; mezinárodní klasifikace nemocí; Verbal Behavior; Remission Induction; Severity of Illness Index; kognitivní poruchy; disociační poruchy; mužské pohlaví; verbální chování; pozornost